Sustained responses to lasmiditan: Results from post-hoc analyses of two Phase 3 randomized clinical trials for acute treatment of migraine - Doty, Erin Gautier; Krege, John H; Jin, Leah; Raskin, Joel; Halker Singh, Rashmi B; Kalidas, Kavita (Cephalalgia, 2019)
Background Sustained pain freedom is an important attribute of acute migraine therapies for patients and physicians. Here we report efficacy of the centrally penetrant, highly selective, 5-HT1F agonist lasmiditan on sustained pain freedom and other outcomes at 24 and 48 hours post-dose. Study design and methods Data from the similarly designed, Phase 3, double-blind studies SAMURAI (NCT02439320) and SPARTAN (NCT02605174) were pooled to more precisely estimate efficacy effects in these post-hoc analyses. In both studies, inclusion criteria were 3–8 migraine attacks per month and Migraine Disability Assessment Score of ≥ 11 (at least moderate disability). Patients were randomized equally to lasmiditan 200 mg, 100 mg, 50 mg (50 mg only in SPARTAN), or to placebo. The study drug was to be taken within 4 hours of onset of pain for non-improving headache of at least moderate severity. Sustained pain freedom was defined as being pain free at 2 hours and at the given time point (24 or 48 hours) post-dose without use of additional study drug or migraine medications. Sustained responses were assessed similarly for most bothersome symptom-free, total migraine-free, and disability-free outcomes. For comparisons with previously published data on other acute medications, an additional endpoint of modified sustained pain freedom at 24 hours was defined as being pain free at 2 hours and no moderate-to-severe headache at 24 hours post-dose without use of additional study drug or migraine medications. Results Significantly higher proportions of patients treated with lasmiditan versus placebo achieved headache pain freedom at 2 hours post-dose: 200 mg: 35.6%; 100 mg: 29.9%; 50 mg: 28.6%; placebo: 18.3% (all p < 0.001). Sustained pain freedom was significantly higher in patients treated with lasmiditan versus placebo at 24 hours: 200 mg: 21.2%; 100 mg: 16.9%; 50 mg: 17.4%; placebo: 10.3% (all p < 0.01); and at 48 hours: 200 mg: 18.4%; 100 mg: 15.2%; 50 mg: 14.9%; placebo: 9.6% (all p < 0.05). Similar sustained benefits of lasmiditan versus placebo at 24 and 48 hours were noted for most bothersome symptom-free, total migraine-free and disability-free responses. Modified sustained pain freedom at 24 hours was also observed in significantly higher proportions of lasmiditan-treated patients versus placebo: 200 mg: 27.0%; 100 mg: 21.7%; 50 mg: 21.7%; placebo: 12.9% (all p < 0.01). Conclusion Sustained responses at 24 and 48 hours were noted in significantly more patients treated with lasmiditan versus placebo for several efficacy outcomes including pain freedom, most bothersome symptom-free, total migraine-free and disability-free responses. Clinicaltrials.gov identifier numbers SAMURAI: NCT02439320; SPARTAN: NCT02605174.